Skills requirements in South African supply chains: A higher education perspective - Luke, R.; Heyns, G.J. (South African Journal of Higher Education, 2019)
In recent years, South African supply chains have struggled to move domestic and international freight efficiently and effectively. The purpose of this paper is to determine the skills that students believe are required in the industry to determine whether there is a mismatch between the supply and demand of supply chain management skills. The findings from this research suggests that, whilst industry has a need for technical (hard) skills, there is a stronger requirement for soft skills, which largely appear to be undervalued by students. This suggests that current curriculums focus on hard skills and do not meet the skills sets required by industry and provides evidence of gaps within the current supply chain education programmes. This research provides an original contribution in that it is the only survey which gauges students’ perspectives on logistics and supply chain requirements in South Africa and compares them to industry perspectives to provide a comprehensive overview of supply chain education in South Africa.